Toward Ecological Equity in the Developing Asean Carbon Market: A Comparative Legal Analysis of Regulatory Reform - Alya Maya Khonsa Rahayu; Adi Sulistiyono; Sapto Hermawan; Seguito Monteiro (Jurnal Hukum, 2026)
The urgency of climate mitigation in Southeast Asia, particularly in Indonesia, Vietnam, Thailand, and Malaysia, drives the need for carbon market frameworks that balance economic goals with ecological equity. Despite rapid development, a significant research gap persists in integrating ecological justice principles, especially indigenous rights and equitable benefit-sharing. This study examines ASEAN carbon market regulations and proposes legal reforms for more inclusive governance. The main objective of this study is to analyze the extent to which ASEAN carbon market regulations accommodate ecological justice principles through a normative juridical approach and to propose targeted legal reforms. The findings reveal that ASEAN carbon market regulations have established a legal basis for emissions trading but remain fragmented in protecting indigenous rights, ensuring equitable benefit-sharing, and integrating ecological justice principles. This study contributes by developing a comparative normative framework that links ecological justice with regional carbon market governance. Normatively, this study proposes targeted legal reforms to strengthen ecological equity: mandatory FPIC for indigenous rights, enforceable benefit-sharing mechanisms, standardized social-ecological justice benchmarks in ASEAN’s carbon framework, and enhanced transparency through public registries. These reforms provide a legal foundation for harmonizing ASEAN carbon market governance while advancing equitable and sustainable climate mitigation.